Simultaneous determination of six antibiotics in human serum by high-performance liquid chromatography with UV detection - Roth, Thomas; Weber, Lea; Niestroj, Marion; Cipa, Franziska; Löscher, Astrid; Mihai, Sidonia; Parsch, Hans (Biomedical Chromatography, 2020)
Antibiotics are widely used in intensive care patients to treat severe infections. To avoid bacterial resistance or toxic side effects, the determination of serum concentration of ABs is advisable. Therefore, in this study, we developed and validated a simple and fast high-performance liquid chromatography method with UV detection for the simultaneous determination of four β-lactam ABs (meropenem, imipenem, ceftazidime, and piperacillin) and two coadministered substances (cilastatin and tazobactam) in human serum. Sample preparation required a simple protein precipitation by methanol. The separation of the ABs occurred within a timeframe of 17 min. For this purpose, we used a Kinetex F5 column with a linear gradient of acetonitrile and phosphate buffer (pH 6.9). The UV detector recorded two separate chromatograms at 220 and 295 nm simultaneously. Validation has demonstrated that the method is linear, accurate, and precise within the clinically relevant range for each substance.
CRIS-Team Scopus Importer:2020-12-04
Keywords: HPLC/UV; human serum; stability of antibiotics; therapeutic drug monitoring; β-Lactam antibiotics